2007
DOI: 10.1002/prot.21731
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating biochemical information and backbone flexibility in RosettaDock for CAPRI rounds 6–12

Abstract: In CAPRI rounds 6-12, RosettaDock successfully predicted 2 of 5 unbound-unbound targets to medium accuracy. Improvement over the previous method was achieved with computational mutagenesis to select decoys that match the energetics of experimentally determined hot spots. In the case of Target 21, Orc1/Sir1, this resulted in a successful docking prediction where RosettaDock alone or with simple site constraints failed. Experimental information also helped limit the interacting region of TolB/Pal, producing a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 46 publications
0
52
0
Order By: Relevance
“…These methods have been intentionally developed to be versatile and can be used in conjunction with ensembles derived from a wide variety of sources, including NMR data, MD simulations, loop ensembles, and homology modeling. Local docking using RosettaDock is featured in a number of successful CAPRI strategies; 27,28,53,61 given the substantial improvements in performance over the standard RosettaDock algorithm, the new methods are a significant step forward in the state of the art of protein-protein docking towards general flexible docking. Incorporation of backbone conformational plasticity into docking might ultimately allow us to expand the list of "dockable" components beyond high-resolution crystal structures to lower-resolution electron microscopy structures, NMR structures, and homology models, which will be essential to applying predictive docking towards a structural understanding of protein interactions in conjunction with ongoing genomic and proteomic efforts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods have been intentionally developed to be versatile and can be used in conjunction with ensembles derived from a wide variety of sources, including NMR data, MD simulations, loop ensembles, and homology modeling. Local docking using RosettaDock is featured in a number of successful CAPRI strategies; 27,28,53,61 given the substantial improvements in performance over the standard RosettaDock algorithm, the new methods are a significant step forward in the state of the art of protein-protein docking towards general flexible docking. Incorporation of backbone conformational plasticity into docking might ultimately allow us to expand the list of "dockable" components beyond high-resolution crystal structures to lower-resolution electron microscopy structures, NMR structures, and homology models, which will be essential to applying predictive docking towards a structural understanding of protein interactions in conjunction with ongoing genomic and proteomic efforts.…”
Section: Resultsmentioning
confidence: 99%
“…This model dictates that the bound conformation of a protein exists in response to the presence of the partner in complex, so the backbone conformational space must be sampled explicitly during docking in response to local energetics of the interface. Explicit backbone flexibility has been modeled primarily using MD, [22][23][24] energy minimization, 23,25 or gradient-based methods in MC minimization, 26,27 but not FFT-based methods. Wang et al have shown impressive results in docking proteins in which a loop undergoes moderate to large conformational changes upon binding using explicit backbone flexibility, but their methods are extremely computationally intensive and require prior knowledge of the flexible regions, limiting their use in blind structure prediction.…”
Section: Introductionmentioning
confidence: 99%
“…9D). The 2 models were within the top 10 of the most probable structures after running the Rosetta docking server (52). The AUC analysis of the PPCA-NEU1 mixture suggests the existence of only one PPCA-NEU1 heterodimeric complex.…”
Section: Figure 3 Half-life Of Endocytosed Neu1 In Ppcamentioning
confidence: 96%
“…After visualization of the contacts and preliminary analysis of the surface interactions with the computer graphics program COOT (49), several three-dimensional models were suggested based on the optimal packing of the individual monomers. Attempts were undertaken to discriminate between various models using the protein-protein docking servers ClusPro (50), RosettaDock (51,52), and Gramm-X (53, 54), with the knowledge-score algorithms based on surface complementarity, energy optimization, and fast Fourier transformation methodologies, respectively.…”
Section: Structural Modeling Of the Neu1 Oligomer And The Heterodimericmentioning
confidence: 99%
“…This poses a challenge due to the 90 M Ube2g2⅐Ub binding affinity, which is weaker than most protein-protein complexes successfully predicted using standard RosettaDock (34). Nevertheless, RosettaDock can take fruitful advantage of cases in which biochemical information (43,44) or multiple/flexible backbone conformations can be incorporated (35,36,44). We have addressed the challenge posed here by low binding affinity by utilizing NMR CSP and PRE measurements to guide sampling toward physically realistic solutions and by allowing for the known flexibility of the ubiquitin C-terminal tail.…”
Section: Ube2g2 Interacts With Both Ubiquitin and Diubiquitin Speciesmentioning
confidence: 99%